Life-Threatening and Suspicious Lesions Caused by Mechanical Cardiopulmonary Resuscitation. (September 2017) - Milling, Louise; Leth, Peter Mygind; Astrup, Birgitte Schmidt
Abstract : Abstract: Chest compression devices for mechanical cardiopulmonary resuscitation (CPR) have become more common. Here, we report the case of a young woman who attempted resuscitated with LUCAS™2 after she was found unconscious at home. At autopsy, we found extensive intramuscular hemorrhages in posterior neck, between the scapulae, and in the lumbar region. Investigation of internal organs showed injuries to the lung, spleen, and kidney. The extension of the injuries gave rise to suspicion of homicide by smothering, which police investigation subsequently did not support. The pattern of injury could be attributed to automatic compression decompression CPR with LUCAS™2. The injuries may have been lethal had the patient survived. For the forensic pathologists, it is important to remain updated on developments in treatment techniques to avoid pitfalls when interpreting injury. Larger studies, prospective or retrospective, may be able to qualify the possible risks of automatic compression decompression CPR even further.